The Influence of Wet Aging on pH, Meat Color, Fat Color and Water Holding Capacity of Bali Beef from Traditional Slaughterhouses in Lombok - Fitriani, Baik Mesy Darita; Dahlanuddin, Dahlanuddin; Fahrullah, Fahrullah; Bulkaini, Bulkaini; Ashari, M; Firhamsah, Ikhwan; Gifari, Zaid Al (Jurnal Pijar Mipa, 2025)
Beef quality plays a vital role in ensuring consumer satisfaction and market competitiveness, particularly in regions where traditional slaughtering practices remain prevalent. This study aimed to evaluate the physical quality of Bali beef obtained from traditional slaughterhouses on Lombok Island and to determine the effect of wet aging on meat quality. The experiment used longissimus dorsi muscle samples from 1 to 3-year-old male Bali cattle. Physical parameters analyzed included pH, meat color, fat color, and water-holding capacity (WHC). Data were analyzed using a Factorial Completely Randomized Design followed by Duncan’s Multiple Range Test. Results showed that wet aging had a significant effect (p<0.05) on most physical parameters. The pH decreased from 5.85 to 5.57, meat color became slightly darker due to myoglobin oxidation, and fat color became lighter under vacuum conditions. WHC increased from 47.13% to 50.34%, indicating improved water retention. Based on these findings, it can be concluded that beef from traditional slaughterhouses in Lombok still meets the quality standards of fresh meat. Furthermore, the 21-day wet aging process significantly enhanced the physical quality of Bali beef without causing adverse effects, demonstrating its potential as a practical post-slaughter treatment to improve the competitiveness of local beef products.